DETERMINATION OF DULOXETINE AND ITS MAJOR METABOLITES IN RABBIT PLASMA BY HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
A rapid and sensitive high performance liquid chromatographic method is described for simultaneous determination of duloxetine and its major metabolites, such as 4- hydroxy duloxetine (M7), Glucuronide conjugate of 5-hydroxy-6-methoxy duloxetine (M6) and Glucuronide conjugate of dihydrodiol duloxetine (M12) in rabbit plasma. HPLC analysis was carried out on a µ-Bondapak C18 column (250 mm × 4.6 mm, 5µm particle size) using methanol: phosphate buffer (pH 7.9, 50 mM) (7:3 v/v) as the mobile phase at a flow rate of 1.5 ml/min. Detection was carried out at 224 nm with an UV detector. The above metabolites present in the rabbit plasma were characterized by retro-synthesis followed by NMR and MS study for structure confirmation and finally injected separately into the HPLC system. All the three retention time matches with the metabolites present in the plasma sample.